Stability analysis of calibration factor for absorbed dose in water (ND,w) in famer type ionization chambers using 10 years historical data - Kanphet, Jaruek; Saenkla , Warocha; Tawonwong, Tanawat (The Thai Journal of Radiological Technology, 2024)
Background: The calibration factor (ND,w) is an important value related to the amount of radiation given to patients receiving radiation therapy. The ND,w value is obtained by sending an ionization chamber to take the calibration examination at the Department of Medical Sciences Ministry of Public Health approximately every 2-3 years frequently. Still, due to the COVID-19 outbreak situation, the calibration appointment has been delayed. This makes it necessary to consider the discrepancy in calibration factor values that may occur during the period that has not yet been sent for calibration. Objective: This study considered the tolerance values. Historical analysis of ND, w values over 10 years of 2 types of ionization chambers. Methods: Analysis of ND,w values over 10 years of 2 types of ionization FC65_G and FC65_P, including a total of 4 ionization chambers that are most used in radiotherapy. Results: Found the change in ND,w values was within the range less than ±3 % allows us to be confident that throughout 10 years it has a relatively high stability Conclusion Famer chamber has a relatively constant calibration factor, meaning that the radiation measurement performance of all chamber is relatively stable. Therefore, it is believed that during the period when the chamber cannot be calibrated, which may be more than 3 years per round of sending, the Famer chambers can still be used to measure radiation accurately.